Public value management, measurement and reporting - Russo, Salvatore (Bingley, U.K. : Emerald, 2014)
This volume aims to shed light on how public service value is identified, managed, measured and reported. The concept of public value has been increasingly associated with the process of modernisation and in recent years the debate has shifted away from 'what' to 'how' public value is conceptualised and practiced. How the public sector can meet the communities' expectations is particularly relevant in light of the Global Financial Crisis. At present, many governments are involved in reform aimed at improving the effectiveness, efficiency and economy of operations, and improving the quality of public services. Examining the effectiveness of these reforms and understanding the gap between the expectations of society and the resources available for public services is an important but under-explored topic. The chapters are the result of a series of conferences and workshops on public value held in 2012 and 2013. There are 20 papers, covering a range of topics, including theoretical reflections, practical case studies and empirical observations aimed at understanding the concept of public value.
Public value management : challenge of defining, measuring and reporting for public services / James Guthrie, Salvatore Russo -- Beyond new public management : does performance measurement drive public value in networks? / Suresh Cuganesan, Kerry Jacobs, David Lacey -- Performance measurement of local public service networks / Steve Martin, James Downe -- Developing strategy to create a public value chain / John Dumay -- Public value as performance : Politicians' and managers' perspectives on the importance of budgetary, accruals and non-financial information / Mariannunziata Liguori, Mariafrancesca Sicilia, Ileana Steccolini -- The quest for public value in the Swedish museum transition / Kerstin Thomson, Mikael Holmgren Caicedo, Maria Mårtensson -- Performance management systems and public value strategy : a case study / Enrico Bracci, Enrico Deidda Gagliardo, Michele Bigoni -- Strategic practices of creating public value : how managers of housing associations create public value / Kim van Eijck, Berit Lindemann -- Conceptual framework and empirical evidence of public value : the case of the Italian higher education sector / Guido Modugno, Giulia Ventin, Giulio Curiel -- Politics and public services : looking beyond economic rationality and public value / Patrizio Monfardini, Pasquale Ruggiero -- Harmony in hierarchy? How politicians and public managers prioritize crucial public values / Zeger Van der Wal -- Co-governing public value in local authorities / Francesco Badia, Elena Borin, Fabio Donato -- Public (dis)value : a case study / Paolo Esposito, Paolo Ricci -- Measuring public value in bureaucratic settings : opportunities and constraints / Enrico Guarini -- Public value theory in the context of public sector modernization / Giuseppe Marcon -- How do we measure public value? From theory to practice / Alessandro Spano -- Sustainable public value inscriptions : a critical approach / Federica Farneti, John Dumay.
Print version record
Keywords: Political Science -- Public Affairs & Administration; Public administration; Public administration -- Evaluation; Public administration -- Case studies; Government productivity